EFEKTIVITAS MODEL PENGINTEGRASIAN STRATEGI AFEKTIF DALAM PEMBELAJARAN MATAKULIAH WICARA INDIVIDU PRODI PENDIDIKAN BAHASA DAN SASTRA IKIP BUDI UTOMO MALANG - Artifa Soraya (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2018)
Learning strategies are steps taken by students to improve their own learning. Learning strategy is desired learners to achieve certain goals and manifest in various types. The use of this learning strategy appears in the specific actions or behaviors that the learners do to improve their language skills, for example by imitating, repeating, transferring into other languages, improving speech, asking for clarification, and so on. This research is more emphasis on affective strategy. This strategy refers to feelings, attitudes, motivations and values. There are three main sets of affective strategies (demeaning your worries, pushing yourself, and getting your emotional temperature). The general objective of this research is to describe the effectiveness of the model of affective strategy integration in learning subject course of Indonesian language and literature study program IKIP Budi Utomo Malang. Specifically, the purpose of this study is to obtain a significant description of the difference between the verbal skills in the 2014A and 2014B classes of Indonesian language and literature education programs IKIP Budi Utomo Malang and obtain a significant description of the difference in effectiveness between the learning ability of speech before and after. This research uses experimental design with non equivalent control group design. The data analysis technique used to find the difference is using paired paired t test formula for one sample and t test of the independent variable for different samples. The sample of this research is student of class of 2014A and 2014B of Indonesian language and literature education program IKIP Budi Utomo Malang. Experiments were conducted by dividing experimental and control groups. The experimental group is a student of Indonesian language and literature education program class of 2014A, while the control group is a student of language and literature education program class of 2014B, by taking pretest value and postes value. Based on the research that has been done, the result of pretest in the experimental group is still low with an average of 56,375 after being given affective strategy treatment on average value rose 20,25 points to 76,625, while the mean in control group at pretest 58,38 up 0,222 points at the postes being 58.61. The effectiveness between the postes value of the experimental group and the control group is very different. In the control group the score also increased but more increase in the experimental group. It shows the model of affective strategy integration in learning subject course of individual speech of Indonesian language and literature education program IKIP Budi Utomo Malang. From the research findings, the researcher suggested that lecturers in the environment of IKIP Budi Utomo Malang should implement learning strategies to improve student achievement and students do not feel bored.